FLORISTIC, STRUCTURAL AND QUALITATIVE CHARACTERIZATION OF A DECIDUAL FOREST FRAGMENT, IN NORTHERN RIO GRANDE DO SUL - Maffra, C. R. B. (Revista Brasileira de Engenharia de Biossistemas, 2019)
The aim of this study was to carry out the floristic, structural and qualitative characterization of a Deciduous Forest fragment, in the region of Alto Uruguai, in Frederico Westphalen-RS. For the vegetation sampling, a permanent of 100 x 100 m, composed of 100 subunits of 10 x 10 m, was installed. All individuals with CBH≥31.4 cm were measured and identified in gender, species and botanical family. The structure was characterized in terms of density, dominance, frequency and importance value index. In the qualitative characterization, the shafts were visually qualified for shape and sanity. In total, 580 individuals were evaluated, and among these, 49 genera, 57 species, 28 botanical families and only 1 unidentified species. Fabaceae was the family that most stood out in number of genera (n=9), species (n=10) and individuals (n=146). The species Trichilia claussenii C. DC., Nectandra megapotamica (Spreng.) Mez e Holocalyx balansae Micheli, with IVI values of 14.0%, 9.1% and 7.3%, respectively, were the most important of the forest fragment. As to the vertical structure, 95.2% of the individuals belong to the inferior and middle strata. In terms of numbers of individuals and dominance, the species that stood out were T. calussenii in the inferior stratum (26.8% and 21.5%), N. megapotamica in the middle stratum (19.4% and 13%) and the H. balansae in the superior stratum (25.0% and 32.9%). The forest fragment is characterized by presenting individuals with slightly tortuous and healthy shafts, without the incidence of damages that may prevent a possible timber use.